Bilateral Globus Pallidus Interna Deep‐Brain Stimulation in a Patient With Myoclonus‐Dystonia: A Case Report. Issue 8 (25th February 2014) - Kim, Ji Hee; Na, Young Cheol; Lee, Won Hee; Chang, Won Seok; Jung, Hyun Ho; Chang, Jin Woo
<x xml:space="preserve">Abstract</x> Objective Myoclonus‐dystonia is a movement disorder characterized by childhood onset of myoclonus and dystonia. We report a case of the epsilon‐sarcoglycan mutation‐negative myoclonus‐dystonia patient who underwent bilateral globus pallidus interna deep‐brain stimulation with subsequent improvement of both myoclonus and dystonia. Case Report A 37‐year‐old woman with myoclonic jerks and dystonia affecting predominantly the lower limbs was treated with chronic bilateral globus pallidus interna deep‐brain stimulation. Results The movement subscore of the Burke‐Fahns‐Marsden Dystonia Rating Scale was 38 before surgery and improved to 7 after 3 years. The disability subscore of the Burke‐Fahns‐Marsden Dystonia Rating Scale improved from 7 to 2. The Unified Myoclonus Rating Scale also decreased significantly from 93 to 39. No hardware‐ or stimulation‐related complications occurred during follow‐up. Conclusion This report suggests that patients with myoclonus‐dystonia may significantly benefit from bilateral globus pallidus interna deep‐brain stimulation. Larger studies of this patient population are needed to confirm the optimal target.